2011
DOI: 10.22358/jafs/66206/2011
|View full text |Cite
|
Sign up to set email alerts
|

The effect of live yeast, <i>Saccharomyces cerevisiae</i>, and their metabolites on ciliate fauna, fibrolytic and amylolytic activity, carbohydrate digestion and fermentation in the rumen of goats

Abstract: The influence of live Saccharomyces cerevisiae cells and their metabolites on the number of ciliates and some fibrolytic and amylolytic enzymes, together with the effect on the concentration of volatile fatty acids (VFA), and disappearance of dry matter (DM) and structural carbohydrates in the rumen of three goats was examined. The control diet (1.2 kg DM·d -1 ) was composed of hay (63%), barley meal (31%), and soyabean meal (4%). Two experimental rations consisting of the same components supplemented with eit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 22 publications
0
8
1
2
Order By: Relevance
“…In the present study, the total VFA concentration was low in comparison with results reported by Kowalik et al (2011) for goats fed diets containing 523 g NDF per kg of dry matter. Molar percentages of acetate, propionate and butyrate, as well as the acetate-to-propionate ratio, were not significantly affected by the addition of yeast products.…”
Section: Resultscontrasting
confidence: 86%
“…In the present study, the total VFA concentration was low in comparison with results reported by Kowalik et al (2011) for goats fed diets containing 523 g NDF per kg of dry matter. Molar percentages of acetate, propionate and butyrate, as well as the acetate-to-propionate ratio, were not significantly affected by the addition of yeast products.…”
Section: Resultscontrasting
confidence: 86%
“…The authors found that up to 38% of total cellulolytic activity in the rumen originated from Eudiplodinium maggii, and that this contribution was visibly related to the number of ciliates. Kowalik et al (2011) reported that live S. cerevisiae increase the degradability of structural carbohydrates of meadow hay in the rumen of goats. The authors suggest that live yeast can increase the number of total ciliates and those belonging to the genus Diplodinium.…”
Section: Resultsmentioning
confidence: 99%
“…Brossard et al (2006) failed to observe a significant effect of live yeast on the fibrolytic and amylolytic activity in the rumen of sheep. In contrast, Kowalik et al (2011) showed that a yeast preparation increased the xylanolytic and cellulolytic activity in the rumen of goats. The cell wall of yeast is a rich source of polysaccharides.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations